2017
DOI: 10.1007/s00403-017-1796-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of dermoscopy in the diagnosis of distal lateral subungual onychomycosis

Abstract: Recently dermoscopic patterns, that can be useful in the diagnosis of distal and lateral subungual onychomycosis, were identified. In this study, we aimed to determine the frequency of the defined patterns so far and additionally to identify other patterns that were observed and to investigate the place of these patterns in the diagnosis of Distal Lateral Subungual Onychomycosis (DLSO) in the dermoscopic examination of the patients with pre-diagnosis of DLSO. Patients admitted dermatology outpatient clinic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…The onychoscopic feature of jagged edges with spikes is defined as jagged edges with spikes of the whitish longitudinal lines, seen on the proximal side of the onycholytic area and extending proximally in the nail plate (13). In this study, jagged edges with spikes were seen in 65.5% of the total cases.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The onychoscopic feature of jagged edges with spikes is defined as jagged edges with spikes of the whitish longitudinal lines, seen on the proximal side of the onycholytic area and extending proximally in the nail plate (13). In this study, jagged edges with spikes were seen in 65.5% of the total cases.…”
Section: Discussionmentioning
confidence: 50%
“…Distal irregular termination or a "ruin appearance" refers to the end of the thickened nail plate ending with an irregular and crumbly appearance (13). In this study, distal irregular termination was seen in 82.7% of cases.…”
Section: Discussionmentioning
confidence: 52%
“…Kaynak et al diagnosed 205 patients with DLSO and found that longitudinal striae pattern is observed in 79.5% of the samples, and that jagged edge with spikes pattern is observed in 63.4% of the samples. At the end of the study, they suggested that ruin appearance and punctate leukonychia are identified as dermoscopic patterns with high sensitivity only for DLSO diagnosis (11). In another study by Nargis et al, longitudinal striae and jagged proximal edges were seen in all patients, intermittent spiked pattern was seen in 78.3% of patients, and chromonychia and distal irregular termination were noticed in 38.3% and 11.7% patients, respectively (15).…”
Section: Discussionmentioning
confidence: 92%
“…The second most common pattern was ruin appearance, meaning subungual hyperkeratosis (54.0%) ( Fig. 2) (11). The incidence and distribution of other patterns are shown in Table 2 ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation